PHARMACOLOGICAL POTENTIALITY AND MEDICINAL USES OF IPOMOEA AQUATICA FORSK: A REVIEW - Malakar, Chitrajit; Das Talukdar, Dr. Anupam; Nath Choudhury, Pinak Pani (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â It has been noteworthy from the ancient times; the human race is dependent on the use of traditional plant-based medicines as well as polyherbal preparations. And from the last few decades several research works are carried out which confirms the potentiality of these natural sources as a good source of medications. Ipomoea aquatica was among such plant having good nutraceutical applications and is commonly consumed as a vegetable and is commonly found in tropical Asia, India, Africa and Australia, etc. The plant is considered to be a good source of vitamins, minerals, plant proteins, fibers, etc. as well as the plant is supposed to have tremendous pharmacological importance. The present review aims to present a brief overview of the medicinal use as well pharmacological value of the plant. Keywords: Pharmacological activity, Phytochemistry, Potential uses, Compounds.